Índice de riesgo de la calidad del agua para consumo humano en zonas urbanas del departamento de Boyacá, Colombia, 2004-2013 - Mery Yaneth Dueñas-Celis; Liliana Marcela Dorado-González; Patricia Espinosa-Macana; Sandra Helena Suescún-Carrero (Universidad de Antioquia, 2018)
Introduction: The quality of water for human consumption is a determining factor in the health conditions of populations. The difference between preventing and transmitting waterborne diseases depends on several factors, such as the quality and continuity of the water supply service. Objective: To determine the performance of the índice de riesgo de la calidad del agua (water quality risk index, irca) for human consumption in urban areas of the department of Boyacá from 2004 to 2013. Methodology: Descriptive study. 122 aqueducts of the urban zones of the municipalities of the Boyacá department were included in the irca evaluation. The sample was taken according to established regulations and for this, technicians were trained in environmental sanitation. Physical, chemical and microbiological analyses were carried out (total coliforms, Escherichia coli, visible color, turbidity, pH and free residual chlorine). The variables analyzed were recorded in the water quality monitoring information system for human consumption (sivicap, as per its Spanish acronym). Statistical analysis of central trend measures and averages was also performed. Results: In 2004, in 122 municipalities of Boyacá, 77% had an irca at high risk and 23% at medium risk. Over time, there has been a decrease in the level of risk, 3% had high risk, 14% medium risk, 29% low risk and 54% were without risk in 2013. Conclusions: In the period studied in the department of Boyacá, the irca showed a tendency to decrease, going from high risk to low risk, possibly due to the implementation and intensification of environmental health surveillance actions carried out by the department's Ministry of Health, such as health inspection visits, verification of good health practices, personalized training for treatment plant operators and permanent monitoring.